Developing a Class Scheduling Mobile Application for Private Campus in Tangerang with the Extreme Programming (XP) Model - Jansen Wiratama; Hari Santoso; Clairence (G-Tech: Jurnal Teknologi Terapan, 2023)
Class schedule is one of the important essences in lecture activities. The class scheduling process at STMIK Dharma Putra, a private campus in Tangerang, has several obstacles. The obstacle is class schedules that still need to be distributed to students and lecturers via short messaging applications such as WhatsApp (WhatsApp Group Chat) and email services, resulting in duplicate schedule files. Another obstacle was when revisions to class schedules and re-submissions caused the class schedule files to accumulate (data redundancy). Moreover, the campus reminder activities are carried out conventionally by sending paper photos of the daily lecture schedule via the WhatsApp group. Based on literature studies conducted in previous research, one way to disseminate information that is quite effective and successful in dealing with similar problems is through mobile-based applications. A mobile-based class scheduling application is developed using Flutter tools with an Extreme Programming model to overcome the problem. The final stage of this research is application testing using the User Acceptance Test (UAT) method with the Black-box testing model. From the results of the UAT test, the results obtained were 92.82% with excellent indicators and following user needs.